2020
DOI: 10.1155/2020/3010631
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary and Macular Flow Changes in Nonarteritic Anterior Ischemic Optic Neuropathy (NAION) by Optical Coherence Tomography Angiography (OCT-A)

Abstract: Background. To analyze the blood flow changes of radial peripapillary capillaries (RPCs) and macula with time procession in patients with nonarteritic anterior ischemic optic neuropathy (NAION) by optical coherence tomography angiography (OCT-A). Methods. A total of 21 affected eyes and 19 unaffected eyes from 21 NAION patients were included. Assessments of BCVA, CFP, SD-OCT, and OCT-A were performed on NAION patients at enrollment and at 1-2 weeks, 1-2 months, and 3–6 months after enrollment. Measures of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…While there was no signifcant change in the microcirculation of the superfcial peripapillary retina, the vessel density of the deep optic disc may decline signifcantly [26,42]. Of note, a greater loss of superfcial RPC was demonstrated suggesting a sectoral reduction of RPC as the optic disc edema subsided [44].…”
Section: Onh Octamentioning
confidence: 91%
See 3 more Smart Citations
“…While there was no signifcant change in the microcirculation of the superfcial peripapillary retina, the vessel density of the deep optic disc may decline signifcantly [26,42]. Of note, a greater loss of superfcial RPC was demonstrated suggesting a sectoral reduction of RPC as the optic disc edema subsided [44].…”
Section: Onh Octamentioning
confidence: 91%
“…Controversial results on alterations of macular vessel density have been reported. Liu et al showed a gradual decline in the whole GCC and the corresponding whole superficial vessel density in NAION after 1-2 weeks, which deteriorated at 1-2 and 3-6 months of follow-ups along with the exacerbating superior hemifield defect [ 44 ]. Aghsaei Fard and coworkers reported a significant decline in superficial but not deep macular vessel density in NAION compared with control eyes [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nos últimos anos, diversos estudos utilizando a Angio-TCO analisaram os plexos capilares retinianos macular e peripapilar em doenças neuro-oftalmológicas. Em patologias isquêmicas, como a neuropatia óptica isquêmica anterior não arterítica, redução da pDV e mDV ocorreria principalmente nas fases mais tardias e essas alterações mostram correspondência com as alterações estruturais e funcionais encontradas em outros exames complementares (170,171) . Na atrofia óptica dominante (172) , redução da pDV foi documentada em relação a controles saudáveis, especialmente nos setores temporal e temporal inferior e apresentaram correlação com a AV, exame de CV e pCFNR dos pacientes.…”
Section: Angiotomografia De Coerência óPtica Na Avaliação Dos Capilares Da Retina Em Neuropatias óPticasunclassified